The Effect of TikTok-Based Health Education on Adolescents’ Knowledge and Attitudes Toward HIV/AIDS - Rizka Yulia; Sofia Februanti; Dewi Aryanti (Lambung Mangkurat, 2025)
The adolescent phase is considered sensitive because the decision to engage in sexual behavior can arise and potentially lead to the transmission of diseases such as HIV/AIDS. Lack of information and knowledge about HIV/AIDS among adolescents is one of the reasons why the culture of free sex among adolescents can continue to develop and increase the risk of HIV/AIDS transmission. This study aimed to determine the effect of health education delivered through animated videos on social media on adolescents’ knowledge and attitudes. Method used Quasi-experimental with pretest-posttest with control design. The research was conducted at SMK 4 Tasikmalaya. Sampling was done using probability sampling, consisting of 21 respondents in each group. Statistical tests using dependent t-test and independent t test. There were the mean scores of knowledges and attitude, before and after education in the intervention group and for the control group (p-value 0.000). There was a mean increase in the average score after education between the two groups with a p-value of 0.012 for knowledge and a p-value of 0.021 for attitude. Health education using animated video media on social media can increase adolescents' knowledge and attitudes about HIV/AIDS.